Nitrogen levels and light flux densities on common bean growth and solar energy conversion - Almeida, Alex A. F. de; Lopes, Nei F.; Oliva, Marco A.; Barros, Raimundo S. (Pesquisa Agropecuaria Brasileira, 2014)
Growth and evaluation of efficiency of solar energy conversion were studied in beans (Phaseolus vulgaris L. cv. 'Negrito 897'), grown in the field under three light flux densities (30%, 70% and 100% of sunlight) and three nitrogen levels (0, 30 and 60 kg/ha of N). Crop growth rate, relative growth rate and net assimilation rate increased as a function of light flux density. Relative growth rate, net assimilation rate and leaf area ratio showed strong tendency to decrease with plant ontogeny. Leaf area ratio increased with shading caused by great leaf area with a simultaneous reduction in dry weight of shaded plants. However, leaf weight ratio was not affected by light or nitrogen levels because reduction in both light and nitrogen levels caused a decrease in leaf and plant dry weights. Whereas specific leaf area increased with reduction in light due to increase on leaf area and reduction of leaf dry weight in shaded beans, there was no significant differences due to nitrogen level. There was an enhancement on efficiency of solar energy conversion with the decrease in solar radiation and increase in nitrogen levels.